Impact of Extreme Climate Events on Rice-Based Farming System : Case Study at Bandung District - Elza SURMAINI; R. BOER (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2011)
Bandung District is found to be an area that is vulnerable to the El-Niño Southern Oscillation (ENSO) events. Whenever ENSO occurs, this district is always suffering from drought and flood leading to significant crop production lost. The vulnerable areas to flood and drought are Bojongsoang and Ciparay. The objectives of the study are : a) to identify problems related climate risks in rice-based farming system and the adaptation of mechanism to cope with climate extreme; b) to elucidate relationship of ENSO development with rainfall variability and effect of rainfall to flood and drought occurrences; and c) to evaluate economics loss due to climate extreme. Assessment of farming system at the study sites was conducted using Rapid Rural Appraisal (RRA) method. Farmer’s annual income were analyzed using frequency analysis of gross margin. The results showed that Sea Surface Temperature (SST) in Tropical Pacific has significantly affected on rainfall in Ciparay sub-District. The raise in SST anomaly is clearly a subject to delay the rainy season, to prolong the dry season period, and to decrease rainfall amount up to below normal, while the decreasing of SST anomaly resulting high intensity of rainfall in the rainy season and lower in the dry season. Whenever ENSO occurs, most farmers is always suffering from drought and flood leading to significant crop failure. Most farmers realized that climate has been changed and recently there is a trend uncertainly of rainfall pattern (proved by 84% of respondents). Nevertheless, they are still using traditional way to determine the beginning of planting season. Results showed that Benefit Cost Ratio (BCR) have smaller value in floods and droughts than normal conditions. Annual net income analysis suggests that many farmers will have negative annual income either at first or second crops fail. Based on the interviews with local authorities and farmers, it is needed to increase awareness of decision maker, extension workers and farmers to climate extremes and to improve their capacity to manage climate risks.